Boosting Scouts’ Interest in English through the Think-Talk-Write Game in Simalungun - Rizky Khairunnisa Sormin; Ika Purnama Sari; Fitri Rizki; Anita Purba; Susiani Susiani (Konsienti : Community Services Journal, 2025)
This activity aims to enhance scout members' interest in learning English in Simalungun Regency through engaging and interactive educational approaches. As English is an international language and a key skill in today’s globalized world, mastering it offers valuable opportunities for communication beyond national borders. As an extracurricular activity, scouting plays a significant role in building students' character, discipline, and social awareness. By combining the values of scouting with English language learning—through methods such as interactive training and evaluations—this program successfully increased both the basic English skills and the motivation of participants while raising awareness of the importance of English proficiency.